The influence of production costs promotional costs and sales volume on profits at PT. Ciomas Adisatwa - Yudha Al Paksi; Dinda Sukmawati Putri; Hieronimus Erwin Indrawan; Mahmud Syarif; Woro Dwi Hartanty (Institute of Computer Science (IOCS), 2023)
PT. Ciomas Adisatwa is one of the most important parts of a series of integrated companies operating in the commercial farm and chicken slaughterhouse (RPA) sector. Under the auspices of PT. JAPFA COMFEED INDONESIA, PT. Ciomas Adisatwa is one of the largest providers of animal protein in Indonesia. The data collection method in preparing this research is the method of observation, interviews, and literature study with the analytical method used is quantitative descriptive analysis, and multiple linear regression testing using SPSS version 25 software, as for several test stages used in this research, namely, test normality, multicollinearity test, heteroscedasticity test, autocorrelation test, partial t test, simultaneous F test, and regression coefficient. The results of the research show that: There is a significant influence of production costs on profits at PT. Ciomas Adisatwa Bogor, there is no significant influence of Promotion Costs on PT Profit. Ciomas Adisatwa Bogor, there is a significant but negative influence on sales volume on PT's profits. Ciomas Adisatwa Bogor.